Developing an Interactive Project Based E-Module for Machine Engineering Subjects for Grade XI Students at State Vocational High Schools - Batistuta, Andreas; Wiratmaja, I Gede; Kusumayani, Ni Made Novia (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This study aimed to develop and evaluate a project-based interactive e-module as a supplementary learning tool for vocational education. The e-module was designed to enhance students' understanding of machining techniques, with a particular focus on lathe machine operations, while improving their ability to apply theoretical concepts in practice. Following the 4D development model like Define, Design, Develop, and Disseminate. the study employed a product development approach. Feasibility assessments by subject matter and instructional media experts yielded scores of 89.16% and 85%, respectively. Practicality evaluations involving small and large student groups achieved scores of 89.66% and 94.66%. These findings indicate the e-module's effectiveness in promoting student engagement and learning outcomes. This research offers a novel approach by integrating project-based learning principles into a digital media complement for machining operations, providing a scalable, interactive, and practical solution to bridge the gap between theoretical knowledge and hands-on skills in vocational education field.